Asthma and COPD patients' perceived link between health literacy core domains and self-management of their condition. Issue 7 (July 2020) - Poureslami, Iraj; Shum, Jessica; Goldstein, Roger; Gupta, Samir; Aaron, Shawn D.; Lavoie, Kim L.; Poirier, Claude; Kassay, Saron; Starnes, Kassie; Akhtar, Alizeh; FitzGerald, J. Mark; ,
Highlights: Patients perceived challenges in self-managing their chronic lung conditions. Access is classified: passive access, active access, and lack of access. Usefulness and truthfulness of information is categorised: pre-use and post-use evaluation. Acquired knowledge informed development of a function-based HL. Abstract: Objective: Health literacy (HL) is a person's ability to practically apply a wide range of cognitive and non-cognitive skills, to make health-related decisions. Currently, no tool applies all HL core domains to capture necessary data to measures HL in adult asthma and COPD patients. We endeavored to develop a comprehensive, function-based tool that adequately and accurately measures HL skills of this patient population. We explored the perspectives of patients related to each core HL domain, with an emphasis on self-management practices. Methods: Sixteen focus groups were conducted (n = 93; 40 asthma and 53 COPD) across Canada. Data was analyzed using NVivo12. Results: Thirteen subthemes were identified within five HL domains: (a) access : active access; passive access; lack of access; (b) understanding : how to improve understanding; (c) trustworthiness ; relevancy and validity of information: pre- and post- application of information; (d) communication : barriers to proper communication; (e) application of information : making health decisions. Conclusions: Participants provided valuable insight in terms of disease management topics and corresponding items to include in our HL tool. Practice implications: Involvement of patients from initial stage allowed us to develop a tool that will serve as a first ever developed HL tool for asthma and COPD patient group.